Cameroun - Marc Pabois (In Situ)
The Ministry of culture in Cameroun asked France for technical assistance to start the inventory of their natural cultural heritage. This implies a number of elements among which: training sessions for cultural executives in the ten provinces, setting up methods and scientific supports for investigation, an inventory of the available documentation to rely on. In such a country with a large oral tradition, it is necessary to give their culture its full dimension and therefore associate ethnologists to the project. Colonial heritage will be studied along with the national one, both being part of Cameroun history. Two places already seem to refer to national heritage: the Kingdom of Idool, east of Ngaoundere and the palace and town of Rey Bouba, south–east of Garoua.